Robotic constructor as a means of teaching C++ programming to high school students - Anton V. Eliseev (RUDN Journal of Informatization in Education)
Problem statement. This paper considers and substantiates approaches to solving the problem of insufficient development of methods for teaching C++ programming to high school students in a computer science course using the VEX EDR robotic constructor. The use of robotic constructors in the school computer science program can significantly improve the process of teaching programming by providing tasks with a practical bias. It also contributes to the development of students’ skills of mutual interaction and independent decision-making, allows to reveal their creative potential in design and design-research activities, and increases their interest in learning computer science, which is especially important in today’s technologically oriented society. The aim of this study is to develop the components of a methodical system for teaching high school students programming in C++ using the VEX EDR robotic constructor and to test the effectiveness of the proposed methodics. Methodology. To achieve the goal, the method of analyzing scientific and methodical sources and normative documents that deal with the problem of teaching programming to high school students within the framework of the computer science course was used. The experimental research was carried out with the participation of two groups of schoolchildren. The control group was taught the topic “Linear Algorithm” in the traditional presentation of the textbook by K.Yu. Polyakov and E.A. Eremin (10-11th grade). The experimental group was taught this topic using the same textbook, but applying a robotic constructor, the developed system of tasks, and methodical recommendations . Results. In the course of the study, it was found that the implementation of the formed components of the methodical system of teaching high school students programming in C++ using the robotic constructor VEX EDR allowed to increase the effectiveness of teaching high school students programming of real performers working ‘in the environment’ . Conclusion. The effectiveness of the developed components of the methodical system of teaching high school students programming in C++ using the VEX EDR robotic constructor has been experimentally proved.